Efektivitas Program MsExel Modifikasi Untuk Meningkatkan Kemampuan Pengelola Adminsitrasi Keuangan - Hani Handayani; Erhamwilda , (Golden Age: Jurnal Pendidikan Anak Usia Dini, 2017)
AbstractThe success of Non-Formal Early Childhood is supported by the proper management of financial administration, but today many PAUD teachers have not yet done so. Efforts to improve the ability of teachers or non-formal early childhood education personnel using computer-based applications, need to be done. The purpose of this research is to develop MS Exel's modified financial program to be more easily applied by PAUD teachers. Development of MS Exel finance program is made because the educational background of most non-formal early childhood teachers is undergraduate. This research was conducted by using a quantitative approach, quasi-experimental method with Pre-Experimental Design (designs). The sample of this study is the administrative staff or PAUD teachers who concurrently duty to be the school administration of 30 people from 30 institutions Non-Formal PAUD existing in District Cimenyan. Program effectiveness is measured by comparing pre-test scores and post-test of respondents' ability in financial administration. The result of the research shows that the hypothetical test calculation is that = 8.6, t price with 5% significance correlation, with point dk = 29 then the price of t table = 1.699, because t count is bigger than the table, then Ho is rejected and Ha is received. This means that there is a significant difference in the ability of respondents in the financial administration of the school between before and after the training. The use of MS Excel Modification program proved to be effective in increasing the ability of teachers or non-formal early childhood education in Cimenyan District in managing financial administration.Keywords: Effectiveness, Ms.Excel Modification, and Financial Administration AbstrakKeberhasilan PAUD Non Formal salah satunya di dukung dengan pengelolaan administrasi keuangan  yang benar, namu saat ini masih banyak guru PAUD yang belum melakukannya. Upaya peningkatan kemampuan guru atau tenaga administrasi PAUD Non Formal dengan menggunakan Aplikasi berbasis komputer, perlu dilakukan. Tujuan penelitian ini adalah mengembangkan program keuangan MS. Exel yang dimodifikasi agar lebih mudah diaplikasikan guru PAUD. Pengembangan program dilakukan, karena latar belakang pendidikan guru PAUD non mayoritas belum Sarjana. Penelitian ini dilakukan dengan menggunakan pendekatan kuantitatif, metode Quasi eksperimen dengan Pre-Experimental Design (nondesigns). Sampel penelitian ini adalah tenaga administrasi atau guru PAUD yang merangkap tugas menjadi administrasi sekolah yang berjumlah 30 orang dari 30 lembaga PAUD Non Formal yang ada di Kecamatan Cimenyan. Efektifitas program diukur dengan membanding skor pre test dan post-test dalam kemampuan administrasi keuangan. Hasil penelitian menunjukkan perhitungan uji hipotesa thitung = 8,6  , harga t dengan korelasi signifikasi  5%, dengan titik dk = 29 maka di peroleh harga  t table =  1.699 ,  karena t hitung lebih besar dari pada ttabel, maka Ho ditolak  dan Ha di terima. Ini artinya terdapat perbedaan yang signifikan dalam kemampuan responden dalam administrasi keuangan sekolah antara sebelum dengan sesudah dilakukan pelatihan. Penggunaan program MS Excel Modifikasi terbukti efektif meningkatkan kemampuan guru ataupun tenaga pendidikan PAUD non formal di Kecamatan Cimenyan  dalam mengelola administrasi keuangan. Kata Kunci: Efektivitas, Ms. Excel Modifikasi, dan Administrasi Keuangan.